Consider the reaction 2NO(g) + O2 ---> 2NO2 (g). The following mechanism has been proposed to explain the experimental rate law:
1. 2NO --> and <-- N2O2 (fast)
2. O2 + N2O2 --> 2NO2 (slow)
Give the rate law for the proposed mechanism. If necessary, use the pre-equilibrium assumption to determine an expression for the concentration(s) of any intermediate(s) that may appear in the derived rate law.
Since step 2 is the rate-determining step, the rate law is
rate = k2[N2O2][O2]...(1)
Now, we need to ...
This solution includes calculations for finding the required rate equation.